Histiocytic lymphoma presenting as a testicular tumour and terminating in acute monoblastic leukaemia. Issue 10 (1st October 2000) - Hull, D R; Alexander, H D; Markey, G M; Lyness, R W; Morris, T C M
Abstract : A 58 year old man presented in 1995 with a swollen testicle. After orchidectomy, a diagnosis of poorly differentiated lymphoma was made. Lymphoid, epithelial, and seminoma markers were all negative. Six months later he developed a buccal lesion, which was biopsied and reported as a high grade non-Hodgkin's lymphoma. It responded completely to chemotherapy but within a year he developed a forearm swelling, which was biopsied and imprints made before fixation of the material. Immunocytochemistry on the imprints showed positivity with antibodies to CD4, CD68, and muramidase, and the non-specific esterase cytochemical stain was strongly positive, leading to a diagnosis of true histiocytic lymphoma. Despite further treatment, the patient entered a terminal acute leukaemic phase, the blasts marking as monoblasts. Review of all the biopsies, including molecular investigations and further immunohistochemistry studies performed retrospectively on the original biopsy, demonstrated that this was the same malignant cell line throughout, and we conclude that this is a case of histiocytic lymphoma, initially presenting as a testicular tumour and terminating in acute monoblastic leukaemia. A diagnosis of histiocytic lymphoma should be considered when lymphoid markers are negative in an apparent lymphoma, but should not be made without recourse to appropriate immunophenotypic and molecular studies.